2021 16th IEEE International Conference on Automatic Face and Gesture Recognition (FG 2021) 2021
DOI: 10.1109/fg52635.2021.9667047
|View full text |Cite
|
Sign up to set email alerts
|

Smile Action Unit detection from distal wearable Electromyography and Computer Vision

Abstract: Distal facial Electromyography (EMG) can be used to detect smiles and frowns with reasonable accuracy. It capitalizes on volume conduction to detect relevant muscle activity, even when the electrodes are not placed directly on the source muscle. The main advantage of this method is to prevent occlusion and obstruction of the facial expression production, whilst allowing EMG measurements. However, measuring EMG distally entails that the exact source of the facial movement is unknown. We propose a novel method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…To reduce the dimensionality and extract the low-dimensional features, a nonnegative matrix factorization was applied to the time-series data of the AUs [44][45][46]. This approach helps obtain interpretable features in a low-dimensional space [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the dimensionality and extract the low-dimensional features, a nonnegative matrix factorization was applied to the time-series data of the AUs [44][45][46]. This approach helps obtain interpretable features in a low-dimensional space [44].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the assessment of facial movements is largely dependent on the target stimuli and their nature [84], but the state-of-the-art AU detection system comparisons provided average F1 scores of .56-.59 [85]. Perusquia-Herna ´ndez et al [46] also indicate the existence of entanglement between upper lip raising (AU10) and lip corner pulling (AU12). Replication studies with a more sophisticated facial movement detection system are awaited.…”
Section: Plos Onementioning
confidence: 99%
“…This allowed us to evaluate the user's physical performance across avatars and conditions. After the experiment, the acquired sEMG values were band-pass filtered from 25 to 200 Hz and the root means square (RMS) was calculated using a sliding window of 100 milliseconds following the methodology used in the study of Perusquía-Hernández et al (2021) [44].…”
Section: Semg Magnitudementioning
confidence: 99%
“…The IBA metric combines a measure of how dominating the class with the highest individual Accuracy rate is with an unbiased index of its Overall Accuracy [45]. Previous studies indicated that all performance metrics, with the exception of the AUC, were weakened by skewed data distributions [61][62][63]. For these reasons, the AUC in addition to the aforementioned metrics were selected to gain a better insight into the performance of the proposed identification system using a specific classifier.…”
Section: Classifiers' Comparisonsmentioning
confidence: 99%